Stability Analysis and Control of a New Smooth Chua's System - Guopeng Zhou; Jinhua Huang; Xiaoxin Liao; Shijie Cheng (Abstract and Applied Analysis)
This paper is concerned with the stability analysis and control of a new smooth Chua's system. Firstly, the chaotic characteristic of the system is confirmed with the aid of the Lyapunov exponents. Secondly, it is proved that the system has globally exponential attractive set and positive invariant set. For the three unstable equilibrium points of the system, a linear controller is designed to globally exponentially stabilize the equilibrium points. Then, a linear controller and an adaptive controller are, respectively, proposed so that two similar types of smooth Chua's systems are globally synchronized, and the estimation errors of the uncertain parameters converge to zero as t tends to infinity. Finally, the numerical simulations are also presented.